2022
DOI: 10.1136/bmjmilitary-2021-002000
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance of military men and women during prolonged load carriage

Abstract: BackgroundThis study evaluated cognitive workload in soldiers undertaking a long duration march wearing different loads.MethodsMilitary participants (n=12 men and n=10 women) performed four 3-hour loaded marches (12.25 km at 4.9 km/hour) wearing either 21 kg, 26 kg, 33 kg or 43 kg. During the march, accuracy and response time were measured using the verbal working memory n-back test (0, 1, 2 and 3) and two bespoke Go/No Go tests (visual/auditory) to assess inhibition of a pre-potent response.ResultsThe physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
4
14
0
1
Order By: Relevance
“…Changes in performance were as high as 20% in some measures. The results supported previous studies that have reported the effects of prolonged exercise [ 17 ] and multi-stress environments [ 23–25 ] on cognitive performance. Armstrong et al [ 17 ] found 20 to 25% decrease in visual Go/NoGO task among men and women during prolonged load carriage and Friedl et al [ 23 ] found a 20% decrease in reasoning during multistressor exposure in summer Ranger training.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Changes in performance were as high as 20% in some measures. The results supported previous studies that have reported the effects of prolonged exercise [ 17 ] and multi-stress environments [ 23–25 ] on cognitive performance. Armstrong et al [ 17 ] found 20 to 25% decrease in visual Go/NoGO task among men and women during prolonged load carriage and Friedl et al [ 23 ] found a 20% decrease in reasoning during multistressor exposure in summer Ranger training.…”
Section: Discussionsupporting
confidence: 91%
“…The results supported previous studies that have reported the effects of prolonged exercise [ 17 ] and multi-stress environments [ 23–25 ] on cognitive performance. Armstrong et al [ 17 ] found 20 to 25% decrease in visual Go/NoGO task among men and women during prolonged load carriage and Friedl et al [ 23 ] found a 20% decrease in reasoning during multistressor exposure in summer Ranger training. These findings highlight the need to understand, prepare and support cognitive performance in military operations in addition to physical and environmental factors.…”
Section: Discussionsupporting
confidence: 91%
“…During the seated condition, participants recorded their answers, while during walking trials, participants were required to relay their answers verbally which were recorded on their behalf. The SDST was designed to be a visual search and inhibition task similar to those tasks previously employed within the literature (Armstrong et al, 2022; Eddy et al, 2015; Kobus et al, 2010). The assessment involved responding appropriately to targets and non-targets.…”
Section: Methodsmentioning
confidence: 99%
“…Failure to maintain performance, in either domain, can result in reduced combat readiness and decreased operational performance (Crawford et al, 2017; Vrijkotte et al, 2016). Consequently, there is growing interest in the relationship between military-specific physical activity and cognitive performance within military operators (Armstrong et al, 2022; Bhattacharyya et al, 2017; Eddy et al, 2015; Giles et al, 2019; Kobus et al, 2010; Nibbeling et al, 2014; Son et al, 2019, 2022; Vine et al, 2021). Despite this interest, the methodologies and approaches used to investigate this relationship have differed considerably, particularly concerning the assessment of cognitive performance.…”
Section: Introductionmentioning
confidence: 99%
“…Responding to a gender data gap in defence that is also evident in wider society, as described in the editorial by Greeves et al ,2 this supplement has been curated to evaluate sex differences in musculoskeletal injuries in training3 and the trained strength,4 the biomechanics of load carriage,5 the cognitive responses to load carriage,6 and the prevalence of, and risk factors for, mental ill-health 7. We also discuss unique challenges for women, including the prevalence of injury and illness on return to work following childbirth,8 and both the prevalence of hormonal contraceptive use9 and influence of hormonal contraceptive use on bone metabolism 10.…”
mentioning
confidence: 99%